2018
DOI: 10.1039/c7sc05378a
|View full text |Cite
|
Sign up to set email alerts
|

C–H activation and nucleophilic substitution in a photochemically generated high valent iron complex

Abstract: The (photo) chemical oxidation of a (TAML)FeIII complex using outer-sphere oxidants results in valence tautomerisation and C–H activation governed by exogenous anions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Earth abundant substitutes, Cu‐ and Fe‐based sensitizers, are already known. Many research groups share the aspiration to create more sustainable versions of photocatalysts, and extensive work is conducted on synthesis and application of earth‐abundant substitutes – copper iron, nickel, vanadium complexes, just to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Earth abundant substitutes, Cu‐ and Fe‐based sensitizers, are already known. Many research groups share the aspiration to create more sustainable versions of photocatalysts, and extensive work is conducted on synthesis and application of earth‐abundant substitutes – copper iron, nickel, vanadium complexes, just to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Choi and coworkers investigated the oxidation of the more toxic As III to As V with a TiO 2 photoanode under both aerobic and anaerobic conditions, with the former being irreversible owing to the more efficient scavenging of conduction band electrons by O 2 . We proposed using a molecular co‐catalyst well known for the efficient mineralization of recalcitrant pollutants, (TAML)Fe V (O) complexes, in a photochemical cycle as part of a PEC for artificial photosynthesis (Figure ) . (TAML)Fe III complexes were pioneered by Collins and his team over several decades and could be activated and oxidized by H 2 O 2 to the Fe V (O) form to fully degrade pollutants such as pentachlorophenol .…”
Section: Pecs For Pollutant Degradationmentioning
confidence: 99%
“…(TAML)Fe III complexes were pioneered by Collins and his team over several decades and could be activated and oxidized by H 2 O 2 to the Fe V (O) form to fully degrade pollutants such as pentachlorophenol . We sought to harness the potent activity of (TAML)Fe V (O) complexes and attempted to use molecular photosensitizers such as Ru(bpy) 3 to photochemically oxidize the precursor . We identified that a potential pitfall could be nucleophilic attack on the unprotected aromatic rings by ions in solution and are now working toward new variants that can be co‐catalysts when deposited on photoanodes in a PEC.…”
Section: Pecs For Pollutant Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Against this backdrop, our group has been actively pursuing photoredox catalytic processes that can generate value‐added organic precursors or degrade pollutants, and can eventually be integrated into AP systems (Figure B). Notably, we developed vanadium(V) photocatalysts ( 2a–2f , Figure S1, Supporting Information) that can selectively cleave the activated CC bond adjacent to the benzylic alcohol in lignin model substrates ( Figure ) .…”
Section: Introductionmentioning
confidence: 99%